Technical Greenhouse-Gas mitigation potentials of biochar soil incorporation in Germany - Isabel Teichmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Biochar is a carbon-rich solid obtained from the heating of biomass in the (near) absence of oxygen in a process called pyrolysis. Its deployment in soils is increasingly discussed as a promising means to sequester carbon in soils and, thus, to help mitigate climate change. For a wide range of feedstocks and scenarios and against the baseline of conventional feedstock management, we calculate the technical greenhouse-gas mitigation potentials of slow-pyrolysis biochar in 2015, 2030 and 2050 when the biochar is incorporated into agricultural soils in Germany and when the by-products from biochar production - pyrolysis oils and gases - are used as renewable sources of energy. Covering the greenhouse gases carbon dioxide, methane and nitrous oxide, our analysis reveals that biochar allows for an annual technical greenhouse-gas mitigation potential in Germany in the range of 2.8-10.2 million tonnes of carbon-dioxide equivalents by 2030 and 2.9-10.6 million tonnes of carbon-dioxide equivalents by 2050. This corresponds to approximately 0.4-1.5% and 0.3-1.1% of the respective German greenhouse-gas reduction targets in 2030 and 2050.
Keywords: Q15; Q24; Q54; 330; biochar; agriculture; Germany; climate change; soil carbon sequestration